The Impact of a 3-Month Behavioral Weight Loss Intervention on Psychological Flexibility and Depression - Samantha J. Schram; Jason Lillis (Behavioral Sciences, 2025)
A significant portion of individuals with overweight or obesity seek behavioral weight loss, which aims to modify behaviors and habits related to diet, physical activity, and lifestyle and has been shown to result in clinically meaningful weight loss and improved cardiometabolic health. While the physical outcomes of behavioral weight loss are well documented, relevant psychological processes and mental health outcomes are less studied. This secondary analysis examined psychological flexibility in relation to depression change and weight change in adults (N = 508) with a body mass index greater than 25 enrolled in a 3-month automated behavioral weight loss intervention. Psychological flexibility was assessed using the Comprehensive Assessment of Acceptance and Commitment Therapy Processes (CompACT), a tool based on Acceptance and Commitment Therapy (ACT) principles. The Patient-Reported Outcomes Measurement Information System (PROMIS) initiative Depression-Short Form, which collects information directly reported by patients, was used to measure levels of depression. Change in psychological flexibility was found to significantly moderate the positive relationship between weight change and change in depression over the course of a 3-month behavioral weight loss intervention, such that individuals with greater increases in psychological flexibility experienced greater reductions in depression levels when also losing weight. These results suggest that psychological flexibility may enhance the psychological benefits of behavioral weight loss and could be a useful target in a modified version of behavioral weight loss intervention.